A Paleolithic Site in the Zagros Mountains of Northern Iraq. Report on a Sounding at Shanidar Cave. I - Solecki, R. S.
Introduction - History - Country - Situation - Survey - Sounding - Layers (A: top layer, B: pits, C, D) - Artefacts (2769 artefacts, 1080 pottery sherds) - Layer A (pottery).